Myeloid derived suppressor cells – a new therapeutic target in the treatment of cancer. Issue 1 (15th July 2013) - Wesolowski, Robert; Markowitz, Joseph; Carson, William E
Abstract : Myeloid Derived Suppressor Cells (MDSC) are a heterogeneous population of immature myeloid cells that are increased in states of cancer, inflammation and infection. In malignant states, MDSC are induced by tumor secreted growth factors. MDSC play an important part in suppression of host immune responses through several mechanisms such as production of arginase 1, release of reactive oxygen species and nitric oxide and secretion of immune-suppressive cytokines. This leads to a permissive immune environment necessary for the growth of malignant cells. MDSC may also contribute to angiogenesis and tumor invasion. This review focuses on currently available strategies to inhibit MDSC in the treatment of cancer.